2016
DOI: 10.1007/s10661-016-5300-9
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruption in Sphoeroides testudineus tissues and sediments highlights contamination in a northeastern Brazilian estuary

Abstract: In recent decades, considerable attention has been devoted to endocrine disruptor chemicals (EDC) and studies on fish feminization have increased throughout the years as a key signal for aquatic environmental contamination. The input of domestic sewage into water reservoirs is common in South American countries, especially in cities that experienced rapid population growths and unplanned urbanization. This study aimed at characterizing morphofunctional parameters of the tropical fish Sphoeroides testudineus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Natural and fecal sterols have been successfully applied to the study of sewage contamination in sediments of tropical and sub-tropical areas (Martins et al , 2014; Venturini et al , 2015; Pimentel et al , 2016). Total sterols (mean values of the seven sterols analyzed (Σ sterols )) ranged from 1,189.53 (C5) to 30,308.02 ng g −1 (C4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Natural and fecal sterols have been successfully applied to the study of sewage contamination in sediments of tropical and sub-tropical areas (Martins et al , 2014; Venturini et al , 2015; Pimentel et al , 2016). Total sterols (mean values of the seven sterols analyzed (Σ sterols )) ranged from 1,189.53 (C5) to 30,308.02 ng g −1 (C4).…”
Section: Resultsmentioning
confidence: 99%
“…Coastal lagoons are located at the terrestrial and marine interface known as the coastal zone, where processes of urbanization lead to the degradation of ecosystems with negative impacts on the quality of habitats and the dynamics of local fauna and flora (Gedan et al , 2010; Pimentel et al , 2016). These aquatic systems are shallow and most of their inputs come from the mainland through rivers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies of Jobling et al (2002) and Osman et al (2015) showed that intersex decreased the fertility of Rutilus rutilus males, resulting in gametes with low motility and, furthermore, low ability for fertilization and decreased viable descendant production. Pimentel et al (2016) characterized the morphofunctional parameters of the tropical fish Sphoeroides testudineus and investigated the eventual occurrence and disruptive endocrine effects on Pacoti River (Ceará, Brazil). Collected fishes were weighed, measured and dissected for the evaluation of gender (male, female, indeterminate) and histological and vitellogenin analyses.…”
Section: General Effectsmentioning
confidence: 99%